2017
DOI: 10.1021/jacs.7b01856
|View full text |Cite
|
Sign up to set email alerts
|

Low-Valent Lead Hydride and Its Extreme Low-Field 1H NMR Chemical Shift

Abstract: Although hydrides of the group 14 elements are well-known as versatile starting materials in many chemical transformations, a hydride of lead in oxidation state II is so far unknown. In this work, we finally complete the jigsaw puzzle by reporting the isolation of the first low valent organolead hydride. The thermolabile dimeric organolead hydride was synthesized at low temperature and features a hydride H NMR signal (in solution 35.61 ppm; in the solid state 31.1 ppm) at the lowest field observed so far for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 58 publications
8
77
0
1
Order By: Relevance
“…The rather high chemical shifts for the hydrides are in agreement with the chemical shift for solid BaH 2 (8.9 ppm) and follow the expected trend for increased deshielding down the group Be to Ba . This has been explained with spin–orbit‐induced‐heavy‐atom effects that strongly increase with the atom number of the heavy atom and is in line with the extreme chemical shift of 35.6 ppm for the hydride in a recently reported ArPbH species …”
Section: Methodssupporting
confidence: 88%
“…The rather high chemical shifts for the hydrides are in agreement with the chemical shift for solid BaH 2 (8.9 ppm) and follow the expected trend for increased deshielding down the group Be to Ba . This has been explained with spin–orbit‐induced‐heavy‐atom effects that strongly increase with the atom number of the heavy atom and is in line with the extreme chemical shift of 35.6 ppm for the hydride in a recently reported ArPbH species …”
Section: Methodssupporting
confidence: 88%
“…We reasoned, however that the ‐OSiMe 3 group in 1 should be useful both as a stabilizing π‐donor ligand (allowing access to low‐valent Ge II compounds), and as an effective leaving group. For example, the first isolable Pb II hydride was recently synthesized using the mild hydride source HBpin and an alkoxide‐substituted Pb precursor (via H − /OR − exchange) …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, no hydroborylation was observed when using 2 as a catalyst, however using the Ge II hydride 3 (10 mol %) as a catalyst revealed stoichiometric (10 %) conversion to Ph 2 C(H)O(Bpin) after stirring overnight. In order to investigate the possible formation of IPr⋅Ge(H)Cl (via OSiMe 3 /H exchange with HBpin), IPr⋅GeCl(OSiMe 3 ) ( 1 ) was treated with a stoichiometric quantity of HBpin (Scheme ); as stated previously, pinacolborane‐mediated alkoxy/hydride exchange is a known route to main‐group hydrides . The resulting product mixture from combining 1 and HBpin yielded the expected siloxyborane Me 3 SiO‐BPin as the sole Bpin‐containing product, along with IPr⋅GeCl 2 and IPrH 2 (Scheme ) as major species .…”
Section: Resultsmentioning
confidence: 99%
“…16 We have also shown that [Pb II ]boryloxides could be obtained as the two-coordinate [Pb(OB{CH(SiMe3)2}2)2] or as the three-coordinate [{2-Me2NCH2C6H4}PbOB{CH(SiMe3)2}2] bearing a bidentate organoligand. 17 Yet, beyond β-diketiminates [3][4][5][6][7][8][9][10][11][12][13][14][15] and bulky terphenyls, [18][19][20] the number of ligands suited to the design of heteroleptic low coordinate lead(II) complexes remains limited. [21][22][23][24][25] In particular, the implementation of potentially bidentate alkoxides for the preparation of soluble heteroleptic lead(II) species only includes a handful of examples, 16,24,26 even if homoleptic [Pb(OR)2]n and [Pb(μ2-OR)N(SiMe3)2]2 alkoxides have been known for some time.…”
Section: Aminofluoroalkoxide Amido and Boryloxo Lead(ii) Complexes † ‡mentioning
confidence: 99%